THE FORM and FUNCTION OF MISRATAH'S COMMERCIAL CENTRE - Blake , Gerald H. Blake (مجلة كلية الاداب, 1968)
With the advent of impressive oil revenues since 1961 the Government of Libya has wisely embarked upon physical planning at national and regional levels. Among the many plans being prepared by everseas consultants at the present time are master plans for the coastal oasis towns of Tripolitania, including El Khums, Zliten and Misratah. (1) Of these Misratah constitutes a challenge of particular interest to the town planner as a result of its early evolution as an oasis market town through to the grandiose expansion of the Italian period. In its ground-plan Misratah illustrates many features of the larger cities of the Arab world which are so often the heirs of different cultures, with a European-style town grafted awkwardly on to a traditional type of Arab town (Figure 1). This arrangement poses many problems for the rationalisation of traffic flows and land use, and in the installation of piped water, electricity and sewerage. The research upon which this paper is based was carried out in 1966 at a time when it was already clear that Misratah was on the verge of great changes. The aim was to examine traditional town country relationships before they become totally obscured, and these functional relationships are clearly reflected in the form of the town's commercial heart. At first sight the layout of Misratah has little to commend it. The street-pattern has clearly developed piecemeal, and on the fringes of the town there is much wasted land. Social facilities such as schools, post office and hospital are scattered inconveniently throughout the new town, but worst of all, there appears to be little to bind the old and the new towns together. It is hoped however that this paper will show that close examination of the central area of Misratah reveals much that is functionally sound, and a focus of interest in the shops and markets which give the town a sense of coherence and unity. When it is remembered that this central area has grown organically with no conscious planning it is remarkable how well it has been adapted to the needs of an oasis market..